TUJUAN DAKWAH DALAM PERSPEKTIF AL-QUR’AN Mempertajam Fokus dan Orientasi Dakwah Ilahi - Iftitah Jafar (State Islamic University North Sumatra, 2010)
Abstract: The Purposes of Religious Mission in Islamic perspective. Many experts has contributed to the formulation of da’wa objectives. Their objectives are mostly based on the people who conduct da’wa activity (dâ’i) or religious organizations that hold da’wa affairs. The objectives can also be designed on the consideration of the audience (mad’u), da’wa approaches as well as contemporary social context. However, as a holy task, da’wa should be based on the objectives that Qur’an proposed. As a book of da’wa, Qur’an pointed some da’wa objectives namely: transforming community from darkness (zulumât) to the divine light (nûr). This can be achieved partly by enhancing people’s faith (îmân) and improving their worship (‘ibâdah). Da’wa is also directed to win God-consciousness (taqwâ) over immoral doings (fujûr) and empowered natural disposition (fithrah). In addition, motivating people to surrender themselve wholly unto God and achieving final spiritual adventure that is piety are other da’wa objectives. Above all, da’wa activities should be focused on the above objectives. Kata Kunci: tujuan dakwah, fithrah insaniyah, dakwah Qur’ani